An Observational Study of Suicide Death in Homeless and Precariously Housed People in Toronto. (July 2017) - Sinyor, Mark; Kozloff, Nicole; Reis, Catherine; Schaffer, Ayal
Objective: Homelessness has been identified as an important risk factor for suicide death, but there is limited research characterising homeless people who die by suicide. The goal of this study is to identify personal, clinical, and suicide method-related factors that distinguish homeless and precariously housed people who die from suicide from those who are not homeless at the time of suicide. Methods: Coroner records were reviewed for all suicide deaths in Toronto from 1998 to 2012. Data abstracted included housing status as well as other demographics, clinical variables such as the presence of mental illness, and suicide method. Results: Of 3319 suicide deaths, 60 (1.8%) were homeless and 230 (6.9%) were precariously housed. Homeless and precariously housed people were each younger than nonhomeless people ( P < 0.0001). Compared with nonhomeless, homeless people were more likely to be male and less likely to be married, to have interpersonal conflict, or to leave a suicide note. Homeless people and precariously housed were more likely to have died by fall/jump than nonhomeless people (62%, 57%, and 29%, respectively). Conclusions: Homeless and precariously housed people are overrepresented among suicide deaths in a large urban center and differ demographically, clinically, and in their suicide method from nonhomeless people who die by suicide. Targeted suicide prevention strategies should aim to address factors specific to homeless people.